HEMOCYTES IN SCORPION- HETEROMETRUS XANTHOPUS - A. E. PATIL,; U. H. SHAH, (The Bioscan, 2012)
The present investigation was undertaken to study the hemocytes in scorpion, Heterometrus xanthopus. Light and phase contrast microscopic observations have shown seven distinct types of hemocytes: 2% Prohemocytes (PRs), 82% Plasmocytes (PLs), 10% Granulocytes (GRs), 2% Spherulocytes (SPs), 1% Adipohemocytes (ADs), 1 % Oenocytoids (OEs), and 2% Coagulocytes (COs). PLs constitutes bulk of the hemocytes in total hemocytes population. The values of THC for male, non pregnant female and pregnant female were 10850 per mm3, 9050 per mm3 and 9760 per mm3 respectively. The males showed higher THC than in non pregnant female. The pregnant females had highest THC value compared to that in males and non pregnant females.